2018
DOI: 10.1111/1556-4029.13747
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lowering the Legal Drink‐Drive Limit on the Toxicological Findings in Driver Fatalities: A Comparison of Two Jurisdictions,

Abstract: In December 2014, the legal blood alcohol limit for drivers in both Scotland and New Zealand was reduced from 80 to 50 mg/100 mL. This paper reports a retrospective study comparing changes in the toxicological findings in deceased drivers and motorcyclists before and after the limit change in both jurisdictions. A year of fatal motor vehicle crashes prior to and following the limit change is examined for both countries. In Scotland, there was an increase in drug prevalence among fatally injured drivers and mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The Department of Forensic Medicine & Science at the University of Glasgow has a contract with the Crown Office and Procurator Fiscal Service (COPFS) to carry out toxicological analyses for postmortem cases in the East and West of Scotland and Dundee, analyzing around 3000 cases per year. These analyses allow the identification and quantitation of alcohol, drugs of abuse, and prescription or over‐the‐counter medications, as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…The Department of Forensic Medicine & Science at the University of Glasgow has a contract with the Crown Office and Procurator Fiscal Service (COPFS) to carry out toxicological analyses for postmortem cases in the East and West of Scotland and Dundee, analyzing around 3000 cases per year. These analyses allow the identification and quantitation of alcohol, drugs of abuse, and prescription or over‐the‐counter medications, as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Three samples were found to contain both classes of drugs in combination with at least one SC. This is consistent with a study investigating toxicological findings in motor vehicle crashes in New Zealand from December 2013 to December 2015 which found that the use of multiple drugs having different pharmacological effects in fatally injured drivers is not uncommon …”
Section: Resultsmentioning
confidence: 99%
“…Sweden's experience was positive in that lowering the legal limit to 20 mg per 100 ml on 1st July 1990, resulted in the 6 years following this to a 9.7% reduction in fatal and single vehicle crashes and a further study by Borschos showed a 10% decrease in fatal crashes [8,9]. In Japan a reduction as in the BAC limit from 50 to 30 mg per 100 ml in 2002, was accompanied by a statistically significant reduction in alcohol involved motor vehicle crashes [10].Similarly, in Southern Taiwan a reduction from 50 to 30 mg per 100 ml in 2013 was responsible for reducing the numbers driving under the influence [11] .However, there are some exceptions including Scotland where the reduction of the BAC to 50 mg per 100 ml in December 2014 was not associated with a reduction in road traffic accidents and in New Zealand where there was an increase in the numbers of deceased drivers and motorcyclists positive for alcohol alone and in those co-using alcohol and drugs [12,13].…”
Section: Bac Levels Worldwidementioning
confidence: 99%